2011
DOI: 10.1016/j.neuropsychologia.2011.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of subtraction and multiplication in the right parietal cortex: Evidence from intraoperative cortical electrostimulation

Abstract: a b s t r a c tPrevious research has consistently shown that the left parietal cortex is critical for numerical processing, but the role of the right parietal lobe has been much less clear. This study used the intraoperative cortical electrical stimulation approach to investigate neural dissociation in the right parietal cortex for subtraction and multiplication. Results showed that multiplication (as well as picture naming) was not affected by the cortical electrical stimulation on all the targeted sites of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 68 publications
(101 reference statements)
0
19
1
Order By: Relevance
“…Two reports have been published on this specific issue. 20,25 In 1 case 25 the authors reported their experience with a patient affected by a right temporal glioma. However, multiplication was not impaired when the right parietal cortex was stimulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two reports have been published on this specific issue. 20,25 In 1 case 25 the authors reported their experience with a patient affected by a right temporal glioma. However, multiplication was not impaired when the right parietal cortex was stimulated.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to electrostimulation mapping of calculation, some experiences have been reported on left parietal lobe mapping, 7,[13][14][15]21,23 while data on right parietal mapping are anecdotal and discordant. 20,25 This difference may be due to the much greater attention given to language mapping so far; however, impairment of mathematical skills can be the cause of serious personal and social difficulties. For this reason, the ability to perform calculation tasks ought to be regarded as a fundamental function.…”
Section: ©Aans 2013mentioning
confidence: 99%
“…Previous studies on simple math with DCE had concerned almost exclusively the left parietal cortex (Whalen et al, 1997;Duffau et al, 2002;Kurimoto et al, 2006;Roux et al, 2009;Pu et al, 2011;Yu et al, 2011), contrasting with only two reports (Yu et al, 2011;Della Puppa et al, 2014), whereby positive sites were found in the right parietal area. In all these studies the classification of errors was missing, and no comparison was ever made between the two hemispheres.…”
Section: Introductionmentioning
confidence: 91%
“…With the same goal, recent studies conducted with direct cortical electrostimulation (DCE) found a role of specific RH areas in simple addition and multiplication (Della Puppa et al, 2013;Della Puppa et al, 2015a;Della Puppa et al, 2015b;Duffau et al, 2002;Roux et al, 2009;Semenza et al, 2016) and subtractions (Yu et al, 2011). Finally, by means of a technique similar to rTMS and DCE (i.e., transcranial direct current stimulation, tDCS) and focusing on the acquisition of mathematical knowledge, Grabner and colleagues (2015) demonstrated that the left posterior parietal cortex is causally involved in arithmetic learning of two-digit operations.…”
Section: Introductionmentioning
confidence: 98%